Avaliação do conhecimento dos docentes de um município do Sudeste brasileiro acerca de traumatismos dentários - Silva, Jéssica Giovani da (2022)
Dental trauma are considered a public health problem and are the second leading cause of dental emergencies with the possibility of irreversible local damage, and the school environment hasthe highest occurrence, which gives teachers the responsibility to adopt the first steps in an attempt to prevent the installation of sequelae. Thus, we intend to evaluate the knowledge of teachers of the municipal school network of Brejetuba-ES, about dental trauma. For this purpose, an observational, quantitative and transversal study was conducted. The sample consisted of 117 teachers, distributed in rural and urban areas. Data collection was done through the application of questionnaires and scripts with images by means of the self-managed technique. The data treatment was done by means of frequency tables with number and percentage, and the analysis was done by means of the IBM SPSS 20 statistical package. The T-test and ANOVA were used to compare the number of correct answers with the independent variables. The results show a deficiency of knowledge in all the scenarios analyzed, with no statistically significant difference between the variables studied. The lack of preparation to deal with it immediately was generally absent, which enables and encourages the installation of sequelae and early dental losses that directly compromise quality of life. Health promotion actions for the dissemination of information are necessary, as well as the insertion of the theme in the curriculum during teacher training, in addition to continued training for those who are already working.